2011
DOI: 10.1177/0310057x1103900516
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Use of Midazolam or Propofol at the End of Surgery May Reduce the Incidence of Emergence Agitation after Sevoflurane Anaesthesia

Abstract: Sevoflurane is associated with a high incidence of emergence agitation in children. Midazolam and propofol have been examined with the aim of reducing emergence agitation after sevoflurane anaesthesia. However, the effect of both drugs on emergence agitation is still controversial. Therefore we designed this study to measure the effect of midazolam or propofol at the end of surgery on emergence agitation during the recovery period. One hundred and one children, aged one to 13 years, undergoing strabismus surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 25 publications
2
40
1
Order By: Relevance
“…They similarly found that propofol and midazolam decreased the incidence of EA by about 40%, but the final incidence of EA in the prophylactic groups was 40%, which is higher than the 15-20% of Chen and colleagues' study. 17 Furthermore, both of these studies compared propofol and midazolam only in patients undergoing ophthalmological surgery. More comparative studies need to be conducted with additional combinations of drugs and in diverse clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…They similarly found that propofol and midazolam decreased the incidence of EA by about 40%, but the final incidence of EA in the prophylactic groups was 40%, which is higher than the 15-20% of Chen and colleagues' study. 17 Furthermore, both of these studies compared propofol and midazolam only in patients undergoing ophthalmological surgery. More comparative studies need to be conducted with additional combinations of drugs and in diverse clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of EA has led many investigators to provide prophylactic treatment, such as propofol, opioid, midazolam, nonsteroidal anti‐inflammatory drugs (NSAIDs), nitrous oxide (N 2 O), ketamine, 5‐hydroxytryptamin 3 inhibitors, magnesium and regional block . Another choice is to use dexmedetomidine, an α 2 ‐adrenoceptor (α 2 ‐AR) agonist with sedative, analgesic and anxiolytic actions, which has been widely used in pediatric and adult populations .…”
mentioning
confidence: 99%
“…An infusion rate of 0.05 μg/kg/min allows for rapid emergence and maintains patient responsiveness . Similarly, one study reported a significantly lower incidence of ED with administration of midazolam (another widely used sedative drug) just before the end of surgery . This was likely due to residual effects of the midazolam during the postanesthesia period.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similarly, one study reported a significantly lower incidence of ED with administration of midazolam (another widely used sedative drug) just before the end of surgery. 15 This was likely due to residual effects of the midazolam during the postanesthesia Values are presented as frequency or mean ± SD. Group R, postoperative infusion of remifentanil 0.05 ug/kg/min; Group C, without postoperative infusion of remifentanil; Et Sevo, endtidal sevoflurane concentration; CI, confidence interval; PADC, postanesthetic discharge score.…”
Section: Discussionmentioning
confidence: 99%